Pengaruh Produk-Produk Gadai, Faktor Bunga, Layanan Pt Pegadaian (Persero) Terhadap Tingkat Pendapatan Usaha Mikro Kecil Dan Menengah Di Kota Mojokerto - Agus Supriyono; Muchtar (Journal of Public Power, 2020)
This study aims to determine the effect and level of influence of Pawn Products, Interest Factors and Services of PT Pegadaian (Persero) Against Levels of Micro and Small Business Revenues in Mojokerto City. The research is an explanatory research (Explanatory Research), using a correlational research survey design. Conceptual framework underlies the submission of hypotheses. Place of research at PT (Persero) Pegadaian Mojokerto with a sample of 100 people. Measurement instruments are given to the sample to obtain research variable data with Linkert scale. The research data were analyzed with multiple linear regression analysis to test the hypothesis. It was found that pawn products, interest factors and PT Pegadaian services significantly simultaneously positively influenced the increase in UMKM revenue with contributions of R = 0,200, F = 1,328 and p = 0,270 <0.01) with a contribution of 20% (R2 = 0.040 ). It is known that the pawn products have a partially positive and significant effect on the increase in UMKM income (β = 0.320, and p = 0, 437> 0.05). It is known that the interest factor partially has a positive and significant effect on UMKM income increase (β = 0.375, and p = 0, 364> 0.05). It is known that PT pawnshop services partially had no effect and significantly on the Increase in UMKM Income (β = -0, 221, and p = 0, 122> 0.05).